Impact of East Asian Summer Monsoon on Surface Ozone Pattern in China. Issue 2 (21st January 2018) - Li, Shu; Wang, Tijian; Huang, Xing; Pu, Xi; Li, Mengmeng; Chen, Pulong; Yang, Xiu‐Qun; Wang, Minghuai
Abstract: Tropospheric ozone plays a key role in regional and global atmospheric and climate systems. In East Asia, ozone can be affected both in concentration level and spatial pattern by typical monsoon climate. This paper uses three different indices to identify the strength of East Asian summer monsoon (EASM) and explores the possible impact of EASM intensity on the ozone pattern through synthetic and process analysis. The difference in ozone between three strong and three weak monsoon years was analyzed using the simulations from regional climate model RegCM4‐Chem. It was found that EASM intensity can significantly influence the spatial distribution of ozone in the lower troposphere. When EASM is strong, ozone in the eastern part of China (28°N ‐ 42° N) is reduced, but the inverse is detected in the north and south. The surface ozone difference ranges from −7 to 7 ppbv during the 3 months (June to August) of the EASM, with the most obvious difference in August. Difference of the 3 months' average ozone ranges from −3.5 to 4 ppbv. Process analysis shows that the uppermost factor controlling ozone level during summer monsoon seasons is the chemistry process. Interannual variability of EASM can impact the spatial distribution of ozone through wind in the lower troposphere, cloud cover, and downward shortwave radiation, which affect the transport and chemical formation of ozone. The phenomenon should be addressed when considering the interaction between ozone and the climate in East Asia region. Key Points: Impact of East Asian summer monsoon intensity on ozone pattern is simulated East Asian summer monsoon intensity can significantly influence the spatial distribution of ozone The chemistry process is the uppermost factor controlling ozone level